Câncer de mama : avaliação da concordância imaginológica e estudo anatomopatológico após quimioterapia neoadjuvante - Oliveira, Silvana Pinheiro de (2005)
The cancer of breast (CB) it is a problem of world public health. One in each eight women will have cancer of breast, becoming like this the most frequent neoplasia among the women. CB it is tied up the feminine identity concerning its potency of orgasm and her sensuality. To elaborate surgical strategic reliable not very aggressive and less mutilate has been search of answers to many researches. Objective: The present study was to evaluate the agreement of the volume of tumor to the evaluation anatomopathological and the diagnosis methods for image dedicated to he/she suckles her: Mammography (MX), Ultra-sound (US) and magnetic Resonance (RMM), in women with cancer of breast locally advanced, submitted to the neoadjuvante chemotherapy. Patient and Methods: 95 women carriers of mammary neoplasia originating from of the national health clinics of the Maternity Escola Assis Chateaubriant (MEAC), Center Regional and Integrated of Oncology (CRIO) and Institute of Cancer of Ceará (ICC) were analyzed at the period of 2003 March to 2005 March. These patient ones were divided in two groups. Treatment Group (TG) with n=46 and Control Group (CG) with n=49. Non parametric analysis correlating the variables was compared with the standard gold, the anatomopathological analysis. Results: The data showed agreement in it analyzes at volumétrica of the imaginológicos methods and the pattern-gold in TG in the following percentages: RMM: 0.70; US: 0.63 and MX: 0.42, when compared to the control group, where were found values of RMM: 0.72; US: 0.70 and MX: 0.41. Conclusion: RMM stopped the largest values of agreement volumétrica in percentile similar in the two groups (GT and GC) and MX, spread image method, offered the smallest indexes of agreement imaginológica when compared with the evaluation anatomopathological. US presented values of agreement satisfactory volumétrica when, compared RMM, should stand out that is method dependent operator.